The activity of disease-causative STING variants can be suppressed by wild-type STING through heterocomplex formation - Shindo, Ruri; Kuchitsu, Yoshihiko; Mukai, Kojiro; Taguchi, Tomohiko (Frontiers in Cell and Developmental Biology, 2022)
Stimulator of interferon genes (STING) is essential for the type I interferon response induced by microbial DNA from viruses or self-DNA from mitochondria/nuclei. Recently, gain-of-function mutations in STING have been identified in patients with STING-associated vasculopathy with onset in infancy (SAVI). The SAVI patients exhibit complex systemic vascular inflammation and interstitial lung disease, resulting in pulmonary fibrosis and respiratory failure. SAVI mouse models have recently developed, harbouring common SAVI mutations, such as N153S and V154M, which correspond to the human N154S and V155M, respectively. Interestingly, crosses of heterozygous SAVI mice did not yield homozygous SAVI mice as of embryonic day 14, indicating that homozygous SAVI embryos were not viable and that wild-type (WT) allele would function dominantly over SAVI alleles in terms of viability. However, the molecular mechanism underlying the dominance has not been understood. In the present study, we show that STING (WT) and STING (SAVI) can form heterocomplex. The heterocomplex localized primarily in the endoplasmic reticulum (ER) and failed to reach the trans-Golgi network (TGN), where STING activates the downstream kinase TBK1. SURF4 is the essential protein functioning in the retrieval of STING from the Golgi to the ER. The amount of SURF4 bound to STING (SAVI) significantly increased in the presence of STING (WT). These results suggest that STING (WT) can suppress the activity of STING (SAVI) by tethering STING (SAVI) to the ER through heterocomplex formation. The dormant heterocomplex formation may underlie, at least in part, the dominance of STING WT allele over SAVI alleles in the STING-triggered inflammatory response.